SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/134830-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Fluid Transfer from Shale Matrix to Fracture Network

Abstract: The objective of this paper is to incorporate a more detailed description of flow in shale matrix to improve modeling of production from fractured shale-gas reservoirs. Currently, most modeling approaches for shale-gas and -oil production are based on the dominance of Darcy flow in both natural fractures and matrix. We improve the description of matrix flow by considering diffusive (Knudsen) flow in nanopores. In our dual-mechanism approach, when Darcy flow becomes insignificant due to nanodarcy matrix permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
105
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(107 citation statements)
references
References 18 publications
0
105
0
2
Order By: Relevance
“…A comprehensive understanding with regard to the complex flow processes as mentioned earlier is certainly required to build a correct mathematical model for shale gas flow. In tight formations like shale gas, the traditional Darcy flow becomes invalid because of the nanodarcy matrix permeability (Ozkan et al 2010). At nanoscale permeability, Knudsen diffusion becomes the dominant mechanism that drives the gas flow from the matrix to the fracture network.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive understanding with regard to the complex flow processes as mentioned earlier is certainly required to build a correct mathematical model for shale gas flow. In tight formations like shale gas, the traditional Darcy flow becomes invalid because of the nanodarcy matrix permeability (Ozkan et al 2010). At nanoscale permeability, Knudsen diffusion becomes the dominant mechanism that drives the gas flow from the matrix to the fracture network.…”
Section: Introductionmentioning
confidence: 99%
“…The shale gas reservoir is isothermal.ˆThere are the no-flow boundaries parallel to the hydraulic fractures at the middle of two fractures in closed reservoir.˜Wellbore storage effect is taken into account. Flow in every region is assumed to be linear similar to the model proposed by Ozkan et al (2010) and is shown in Fig. 2.…”
Section: Model Description Physical Model and Its Assumptionsmentioning
confidence: 99%
“…Considering the limited width of the simulated region, five-region model was defined to simulate the SRV to extend the trilinear model (Stalgorova and Mattar 2012b). Dehghanpour and Shirdel (2011) improved the Ozkan's dual-porosity model (Ozkan et al 2010) to explain the unexpected high gas production in shale gas reservoirs based on the pseudo-steady model of Warren and Root (Warren and Root 1963). Then, equivalent flow model (Ketineni S and Ertekin 2012) was used to describe the SRV and solved the elliptical flow problem by Mathieu modified functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the slip flow and transitional flow are the typical flow regime in shale, which is different from the linear flow equation of conventional gas reservoirs. Ozkan et al (2010) studied the flow mechanisms in shale matrix and micro fracture system [19], and developed a dual-mechanisms model by coupling diffusion with Darcy flow to describe the gas flow in shale matrix. [20].…”
Section: Introductionmentioning
confidence: 99%